Studies on alzheimer's disease - Mecocci, Patrizia; Pratico, Domenico (Oxidative Stress in Applied Basic Research and Clinical Practice, 2013)
This volume systematically reviews the basic science and clinical knowledge of the role of free radicals and antioxidants, collectively known as "oxidative stress," in the pathology of Alzheimer's disease. It describes the most current diagnostic tools, laboratory methods and technology, and suggests ways of prevention and treatment to emphasize the concept of the bench-to-bedside approach. Studies on Alzheimer's Disease provides thorough coverage of emerging technology and medical applications including discussions of biomarkers and antioxidants as therapeutic agents, and several more relevant aspects. In addition, this book promotes the concept of using biomarkers representative of oxidative stress reactions and free-radical damage, as well as describing the effects of antioxidants in treating disease in clinical trials. This content is invaluable to both researchers studying the development of-and clinicians treating patients with a diagnosis of-Alzheimer's Disease.